2006
DOI: 10.1152/japplphysiol.00319.2006
|View full text |Cite
|
Sign up to set email alerts
|

How the body controls brain temperature: the temperature shielding effect of cerebral blood flow

Abstract: . How the body controls brain temperature: the temperature shielding effect of cerebral blood flow. J Appl Physiol 101: [1481][1482][1483][1484][1485][1486][1487][1488] 2006. First published July 13, 2006; doi:10.1152/japplphysiol.00319.2006.-Normal brain functioning largely depends on maintaining brain temperature. However, the mechanisms protecting brain against a cooler environment are poorly understood. Reported herein is the first detailed measurement of the brain-temperature profile. It is found to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 30 publications
9
66
1
Order By: Relevance
“…In mammals, the most important factors are the temperature of the incoming arterial blood, brain metabolism, and external temperature (2). It has been theoretically estimated that the normal human brain produces ca 0.66 J of heat every minute per gram of brain tissue (3).…”
mentioning
confidence: 99%
“…In mammals, the most important factors are the temperature of the incoming arterial blood, brain metabolism, and external temperature (2). It has been theoretically estimated that the normal human brain produces ca 0.66 J of heat every minute per gram of brain tissue (3).…”
mentioning
confidence: 99%
“…Computer simulations in adult (Nelson and Nunneley 1998;Zhu and Diao 2001) and neonatal (van Leeuwen et al 2000) human brain suggest temperature can be substantially different from deep brain values only in the regions near the brain surface. A recently proposed theoretical model Yablonskiy 2004, 2006) experimentally verified in (Zhu et al 2006) attributed this phenomenon to the temperature shielding effect of blood flow. Here, cerebral blood flow (CBF) efficiently protects deep brain tissues from temperature changes by replenishing tissue heat losses to the surroundings.…”
Section: Introductionmentioning
confidence: 93%
“…7a) Although the temperature of mammalian internal organs are considered relatively uniform (and constant), recent studies have shown that significant temperature gradients do occur [7,8,14]; even in a thermally "shielded" organ, brain. Whilst temperature shielding, due primarily to the effects of incoming arterial blood [45] would be expected to obviate large temperature gradients within internal structures, this is not the case for skin.…”
Section: Hcs Process Aided Evaluation Of the Temperature Variation Ofmentioning
confidence: 99%